From words to pixels: The Infectious Diseases in Motion (IDIM) and VACCELERATE experience for fast and accessible science audiovisual communication - Jon Salmanton-García; Janina Leckler; Oliver A. Cornely (One Health, 2023)
Background: The internet's impact on knowledge distribution has led to a growing demand for accessible science information. COVID-19 heightened interest in science, emphasizing the need to combat misinformation. This publication discusses digital scientific outreach, particularly in infectious diseases, to counter misinformation and promote evidence-based communication. Methods: Infectious Diseases in Motion (IDIM) and VACCELERATE use YouTube for infectious diseases and vaccine research dissemination. They create video abstracts by identifying relevant publications, coordinating recording sessions, and producing visually engaging content. Results: As of August 2023, IDIM and VACCELERATE have produced 173 videos, attracting viewers from 34 countries. This global reach supports their role as valuable resources for the international scientific community. Conclusions: The success of these initiatives lies in inclusivity, collaboration, multilingual content, and effective promotion. They aim to become essential hubs for global scientific knowledge dissemination, advancing understanding through shared knowledge.